2021
DOI: 10.1002/sctm.20-0491
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Autologous Synovial Mesenchymal Stem Cells with Trisomy 7 into the Knee Joint and 5 Years of Follow-up

Abstract: Mesenchymal stem cells (MSCs) can show trisomy 7; however, the safety of these cells has not been fully investigated. The purposes of this study were to determine the ratio of patients whose synovial MSCs were transplanted clinically, to intensively investigate MSCs with trisomy 7 from a safety perspective, and to follow up the patients for 5 years after transplantation. Synovial MSCs at passage 0 were transplanted into a knee for degenerative meniscus tears in 10 patients, and the patients were checked at 5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
0
12
0
2
Order By: Relevance
“…Total RNA was extracted from synovial MSCs and HUVECs using an RNeasy Mini Kit (Qiagen N.V.). RNA sequencing was performed as described previously [ 25 ]. Briefly, the RNA concentration and quality were determined using a Quantus Fluorometer (Promega Co., WI, USA) and an Agilent 2100 Bioanalyzer, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from synovial MSCs and HUVECs using an RNeasy Mini Kit (Qiagen N.V.). RNA sequencing was performed as described previously [ 25 ]. Briefly, the RNA concentration and quality were determined using a Quantus Fluorometer (Promega Co., WI, USA) and an Agilent 2100 Bioanalyzer, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Synovial mesenchymal stem cells also harbor a trisomy 7. One can suppose that there is a link between the synovial hyperproliferation, EGFR pathway and TGCT ( 38 , 40 ). The effect of trisomy 5 is uncertain.…”
Section: Genetic Similarities and Differences Between Tgct Ra And Sar...mentioning
confidence: 99%
“…Most studies that have evaluated the oncogenic potential of MSC had a short follow-up, usually only one or two months, which may not be sufficient to detect potential long term oncogenic effects [7,11,12]. In the clinical setting, MSC with trisomy 5 [7] or trisomy 7 [31] has already been injected into humans that were followed up for two and five years, respectively, with no signs of tumor formation. In a recent study, MSCs harboring trisomy 5 were reported incapable of generating colonies in soft agar, therefore lacking the ability of transformed cells to grow in an anchorage independent manner [32].…”
Section: Stem Cells Internationalmentioning
confidence: 99%